2002
DOI: 10.1152/japplphysiol.00972.2001
|View full text |Cite
|
Sign up to set email alerts
|

Gasping and autoresuscitation in the developing rat: effect of antecedent intermittent hypoxia

Abstract: Gasping is a critically important mechanism for autoresuscitation and survival during extreme tissue hypoxia. Evidence of antecedent hypoxia in sudden infant death syndrome suggests that intermittently occurring hypoxic episodes may modify gasping and autoresuscitation. To examine this issue, an intermittent hypoxia (IH) profile consisting of alternating room air and 10% O(2)-balance N(2) every 90 s was applied to pregnant Sprague-Dawley rats (IHRA; n = 50) and to pups after a normal pregnancy (RAIH; n = 50) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 29 publications
3
44
0
8
Order By: Relevance
“…Hypoxia causes a transient tachycardia followed by a parasympathetically mediated bradycardia in vivo (Guntheroth and Kawabori, 1975;Taylor and Butler, 1982;Loewy and Spyer, 1990;Schuen et al, 1997;Slotkin et al, 1997;Deshpande et al, 1999;Gozal et al, 2002). It is important to note that the time course of the changes in spontaneous glycinergic and GABAergic IPSC frequencies in CVNs is strikingly similar to the time course of hypoxiainduced heart rate changes in neonatal rats (Slotkin et al, 1997).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Hypoxia causes a transient tachycardia followed by a parasympathetically mediated bradycardia in vivo (Guntheroth and Kawabori, 1975;Taylor and Butler, 1982;Loewy and Spyer, 1990;Schuen et al, 1997;Slotkin et al, 1997;Deshpande et al, 1999;Gozal et al, 2002). It is important to note that the time course of the changes in spontaneous glycinergic and GABAergic IPSC frequencies in CVNs is strikingly similar to the time course of hypoxiainduced heart rate changes in neonatal rats (Slotkin et al, 1997).…”
mentioning
confidence: 91%
“…Hypoxia initially elicits an increase, followed by a decrease, in respiratory frequency. In addition, hypoxia transforms eupnic respiratory activity to gasping activity, which is characterized by infrequent, robust breaths of short duration (Guntheroth and Kawabori, 1975;Gozal et al, 2002). Prolonged hypoxia eventually produces a terminal apnea.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, respiratory challenges, such as hypoxia or hypercapnia, evoke strong coordinated cardiorespiratory responses. Hypoxia transforms respiration from eupnea to gasping, characterized by a transient increase, followed by a subsequent decrease in respiratory frequency (Guntheroth and Kawabori, 1975;Gozal et al, 2002). In addition, hypoxia and hypercapnia evoke an initial tachycardia, followed by a bradycardia mediated primarily by increases in parasympathetic activity (Taylor and Butler, 1982;Schuen et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment guidelines for pregnant women with OSA are similar to that of the general population because data in pregnant women are limited. Data from animal studies demonstrated fetal growth retardation with maternal hypoxia; [61][62][63] an important goal in pregnant women is to avoid maternal hypoxemia 51 (strength of recommendation, C). CPAP is the standard treatment for OSA among general population 64 (strength of recommendation, A).…”
Section: Treatment Of Osa During Pregnancymentioning
confidence: 99%